UPAYA PENINGKATAN PRODUKTIVITAS DAN PEMASARAN PRODUK KRIPIK BAYAM MELALUI PEMASARAN ONLINE - I Gusti Ayu Wirati Adriati; I Kadek Bagus Mahendrayana; Ida Bagus Teddy Prianthara; I Putu Dharmawan Pradhana; Sahri Aflah Ramadiansyah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Spinach is one of the agricultural commodities that are widely cultivated by farmers. This commodity is better known by the public as a vegetable that is easy to obtain and has many health benefits. The abundance of spinach during harvest in the village of Kumba makes villagers confused about what to process spinach into, there are even farmers who throw their crops into the river due to confusion about what to make in a hydroponic green house. This problem was then used by UNDIKNAS Bali students who had KKN in the village of Kampung Kusamba to create UMKM which would later be run by PKK women. It turns out that this UMKM is still not running optimally due to several problems, so this service aims to. Provide knowledge about operational management, so that it can work effectively and efficiently, and provide knowledge about good marketing management, and the use of social media to support digital marketing. Media promotion can be carried out by utilizing Linktree and Instagram as active promotional media in the field. Then it is necessary to develop business sales by utilizing social media as a forum for product marketing through social media accounts which are promotional platforms. This activity was carried out to help spinach chip business actors to increase sales by introducing ways to use social media as a promotional medium